Anti‐Inflammatory Nanotherapeutics by Targeting Matrix Metalloproteinases for Immunotherapy of Spinal Cord Injury. Issue 41 (12th September 2021) - Shen, Kui; Sun, Guodong; Chan, Leung; He, Lizhen; Li, Xiaowei; Yang, Shuxian; Wang, Baocheng; Zhang, Hua; Huang, Jiarun; Chang, Minmin; Li, Zhizhong; Chen, Tianfeng
Abstract: Neuroinflammation is critically involved in the repair of spinal cord injury (SCI), and macrophages associated with inflammation propel the degeneration or recovery in the pathological process. Currently, efforts have been focused on obtaining efficient therapeutic anti‐inflammatory drugs to treat SCI. However, these drugs are still unable to penetrate the blood spinal cord barrier and lack the ability to target lesion areas, resulting in unsatisfactory clinical efficacy. Herein, a polymer‐based nanodrug delivery system is constructed to enhance the targeting ability. Because of increased expression of matrix metalloproteinases (MMPs) in injured site after SCI, MMP‐responsive molecule, activated cell‐penetrating peptides (ACPP), is introduced into the biocompatible polymer PLGA‐PEI‐mPEG (PPP) to endow the nanoparticles with the ability for diseased tissue‐targeting. Meanwhile, etanercept (ET), a clinical anti‐inflammation treatment medicine, is loaded on the polymer to regulate the polarization of macrophages, and promote locomotor recovery. The results show that PPP‐ACPP nanoparticles possess satisfactory lesion targeting effects. Through inhibited consequential production of proinflammation cytokines and promoted anti‐inflammation cytokines, ET@PPP‐ACPP could decrease the percentage of M1 macrophages and increase M2 macrophages. As expected, ET@PPP‐ACPP accumulates in lesion area and achieves effective treatment of SCI; this confirmed the potential of nano‐drug loading systems in SCI immunotherapy. Abstract : Herein a polymer‐based nanodrug delivery system conjugating with matrix metalloproteinases (MMPs)‐responsive molecule and activated cell‐penetrating peptides is constructed to enhance the ability for diseased‐tissue targeting. This nanosystem targets the injury site through penetrating the blood‐spinal cord barrier, regulates the polarization of macrophages in lesion area, and exerts neuroprotective effects to promote locomotor recovery.